UNDERSTANDING THE RELATIONSHIP BETWEEN HUMAN RESOURCES MANAGEMENT (HRM), HUMAN RESOURCES MANAGEMENT PRACTICES (HRMP) AND EMPLOYEE ENGAGEMENT - Kumar Kundu, Anjan (International Journal of Psychosocial Rehabilitation, 2024)
The connection between Human Resources Management Practices (HRMP) and employee engagement hasacquired critical consideration structure researchers. Regardless of the significance of HRMP and its effecton employee engagement in the business, little examination has been done as far as developing a deliberatewriting audit in the branch of knowledge. Subsequently, this paper intends to introduce a methodical writingsurvey of articles dependent on forty exceptionally positioned diaries during the time of 1990 to 2017. Thepaper researches the chronicled advancements of Human Resources Management (HRM), HRMP, andemployee engagement to introduce the reasonable evolvement and elaboration of the connection amongHRMP, and employee engagement. The writing featured that appropriately executing HRMP impactsemployee engagement, and what this relationship decidedly means for the general presentation. In this term,a proposed system is introduced. At long last, the examination restrictions and roads for future analysts aregiven